IDENTIFIKASI SPERMA PEMBAWA KROMOSOM X DAN Y SECARA MORFOMETRI SEBAGAI DASAR APLIKASI SEXING SEMEN SAPI PASUNDAN (Morphometrics identification of x and y chromosome bearing sperm as a basis for semen sexing application in Pasundan cattle) - Nurcholidah Solihati; Siti Darodjah Rasad; Nena Hilmia Nena Hilmia; Salsa Adila Irianti (Universitas Nusa Cendana, 2023)
Pasundan cattle spread across the West Java region, but their population decreased from 2014 to 2019. Accelerated population increase has been carried out through the artificial insemination (AI) and it is hoped can help meet the need for meat. AI program can be accompanied by the application of sperm sexing so it can meet the sex according to purpose. The method of albumin column is sexing method based on morphometric data. The aim of this research was to identify the X and Y crhomosome bearing sperm morphometrically as a basis for sperm sexing in Pasundan cattle semen. This research used frozen semen from seven Pasundan cattle. Sperm morphometric observations were carried out using an Olympus microscope equipped with the DP2-BSW-E application. The parameters observed included the length, width and area of the sperm head and the proportion of X and Y chromosome bearing sperm. Two straws were used from each bull, each straw was counted as 200 sperm, so the number of sperm measured was 400 sperm per bull. The data was analyzed quantitatively descriptively. The results of measurements on seven males showed that the sperm head of Pasundan cattle had a minimum-maximum length of 7.68 - 11.36 µm; width 3.97 - 6.30 µm; sperm head area 31.09 - 51.12 µm2. The percentage 41.00-55.50% for X- and 44.50-59.00% for Y- chromosome bearing sperm, with average 50.25% for X- and 49,75% for Y-chromosome bearing sperm. It was concluded that the X and Y chromosome bearing sperm have balanced natural proportion, so the sperm sexing needs to be done to increase the chances of birth of the sex according to purpose.